PELUANG PENGHEMATAN ENERGI UAP MENGGUNAKAN METODE NON - INVESTMENT POINT - - Rahmat; Bambang Setyoko; Seno Darmanto (TRAKSI, 2007)
Energy efficiency  of boiler system is the main parameter in depressing of  operational cost. There are two methods to improving efficiency of boiler system. The one is Non-Investment Point method, where not need adding expense to improving energy process by installing of the new equipment in the system ,nevertheless it is significan mean .  From perceiving experience-data sources, about 10 % - 20 % losses can be saved by non-investment point method. Key Word : Boiler, Efficiency, Non-Investment Methode